(untitled) (Research, Society and Development, 2021)
The aim of this study was to compare the efficacy of two different treatment of odontogenic cellulitis in pediatric patients: conservative treatment (just intravenous antibiotic administration and tooth root treatment or tooth extraction) and surgical treatment (intravenous antibiotic administration, incision, drainage and tooth root treatment or tooth extraction). The search strategy was conducted based on the model of systematic review adopted by PRISMA guidelines. The search strategy included: Pubmed/MEDLINE, Web of Science, Scopus and Cochrane Library databases seeking clinical trials with, unless, ten pediatric patients, in English and available on-line. The key-words used in the screening were “Infection Control, Dental and Cellulitis OR odontogenic infection and cellulitis”. A total of 404 studies were obtained and the selection of manuscripts was performed based on the defined inclusion and exclusion criteria and four manuscripts were according with review. It was verified that the surgeons of these studies commonly choose the conservative treatment, varying the adherence rate between 75% and 95.2% and no complications were associated with this treatment. Likewise, 75% of the author support the conservative treatment. The conservative treatment of cellulitis in pediatric patients, presents efficacy without having to submit the patient to surgical drainage.